2017
DOI: 10.4168/aair.2017.9.5.431
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-COPD Overlap Shows Favorable Clinical Outcomes Compared to Pure COPD in a Korean COPD Cohort

Abstract: PurposeComparisons of the characteristics of chronic obstructive pulmonary disease (COPD) and asthma-COPD overlap syndrome (ACOS) have been the focus of several studies since the diseases were defined by the Global Initiative for Asthma and Global Initiative for Chronic Obstructive Lung Disease guidelines. However, no consensus is available yet. In this study, we aimed to compare the characteristics of asthma-COPD overlap (ACO) and COPD.MethodsWe retrospectively reviewed 1,504 patients with COPD in a Korean CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 30 publications
3
20
1
Order By: Relevance
“…The frequency of AE-COPD in the ACOS cohort compared with that in the non-ACOS cohort (eg, patients with only COPD, patients with only asthma and patients without asthma or COPD) that was determined in our study is different from those reported in previous studies. 1 2 24 In our previous study, 7 the frequency of AE-COPD was higher in the ACOS cohort than in the non-ACOS cohort (patients without asthma or COPD). The results of this study revealed that the frequency of CAD and CD events did not differ between the ACOS cohort with a higher frequency of AE-COPD and the non-ACOS cohort (aHRs for CAD and CD=1.05 and 1.11, respectively; all p>0.05).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The frequency of AE-COPD in the ACOS cohort compared with that in the non-ACOS cohort (eg, patients with only COPD, patients with only asthma and patients without asthma or COPD) that was determined in our study is different from those reported in previous studies. 1 2 24 In our previous study, 7 the frequency of AE-COPD was higher in the ACOS cohort than in the non-ACOS cohort (patients without asthma or COPD). The results of this study revealed that the frequency of CAD and CD events did not differ between the ACOS cohort with a higher frequency of AE-COPD and the non-ACOS cohort (aHRs for CAD and CD=1.05 and 1.11, respectively; all p>0.05).…”
Section: Discussionmentioning
confidence: 76%
“…This strategy may have counterbalanced 2 the risk of CAD and CD in the ACOS cohort with AE-COPD. 1 Studies conducted in Korea 1 and Japan 47 have reported that the lung function of patients with ACOS may be recovered by medication. Meanwhile, the ACOS cohort appeared to be more responsive to bronchodilators 34 and inhaled corticosteroids 48 compared with the COPD-only cohort; this finding supports the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COPD with asthma cohort exhibit lower forced expiratory volume in 1 second/forced vital capacity (FEV1/FVC) [12] and eosinophilic inflammation in the airway [54]. In COPD with asthma cohort, ICSs and OSs may attenuate eosinophilic [53] inflammation in the airway [54] and may have the lower frequency of AE [55], thus improving pulmonary function and quality of life. A favorable longitudinal change in lung function in COPD with asthma cohort with ICSs use is the slower decline of lung function (FEV1/FVC) in these patients compared with COPD cohort [13], supporting our result.…”
Section: Discussionmentioning
confidence: 99%